1986
DOI: 10.1073/pnas.83.11.3723
|View full text |Cite
|
Sign up to set email alerts
|

Rat transferrin gene expression: tissue-specific regulation by iron deficiency.

Abstract: Rats raised on a low-iron diet were used as a model system for investigating the regulation of transferrin gene expression by iron deficiency. We quantitated transferrin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
80
1
2

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(85 citation statements)
references
References 34 publications
(40 reference statements)
2
80
1
2
Order By: Relevance
“…This was challenged because humans with atransferrinemia develop iron-overloading rather than iron deficiency [26]. Neither transferrin nor transferrin receptors could be demonstrated in the microvilli of duodenal mucosal cells [27,28], the gene for transferrin was not expressed in intestinal mucosa cells [29], and the absorption of several divalent metal cations which do not bind transferrin in vivo varied inversely with the state of iron repletion in animals. During the past decade two pathways were identified that appeared to facilitate the uptake of dietary inorganic iron into intestinal absorptive cells.…”
Section: Discussionmentioning
confidence: 99%
“…This was challenged because humans with atransferrinemia develop iron-overloading rather than iron deficiency [26]. Neither transferrin nor transferrin receptors could be demonstrated in the microvilli of duodenal mucosal cells [27,28], the gene for transferrin was not expressed in intestinal mucosa cells [29], and the absorption of several divalent metal cations which do not bind transferrin in vivo varied inversely with the state of iron repletion in animals. During the past decade two pathways were identified that appeared to facilitate the uptake of dietary inorganic iron into intestinal absorptive cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lactoferrin (LF) is a multifunctional protein belonging to the transferrin family. The levels of transferrin have been shown to increase in iron deficiency anemia [5,6]. Additionally, incidents of bleeding in cancer patients can result in iron deficiency anemia, which subsequently increases the levels of lactoferrin [79].…”
Section: Introductionmentioning
confidence: 99%
“…The tissue specificity of transferrin gene expression has been quantified in several species. In rats, for example, transferrin mRNA accumulates to a level of 6,500 molecules per cell in liver and roughly 100 molecules per cell in brain and testis, whereas most other tissues have less than 12 molecules per cell (18). Transferrin gene expression has also been studied during fetal development, revealing a pattern of expression that deviates dramatically from the adult pattern.…”
mentioning
confidence: 99%